Variação da cor e propriedades cerâmicas com o aumento da temperatura de queima de uma argila proveniente da formação Corumbataí, região de Piracicaba, SP) - Roveri, C. D. [UNESP] (2007)
The objective of this paper is to understand the influence of the iron contained in the illite, present in the Corumbataí formation, in the color of firing of ceramic products. A sample was selected, with a gray color clearly, with illite domination, hydroxide and oxide percentage and relatively low iron, with basis of petrographics, mineralogical and chemical studies. For the ceramic essays, the test bodies were fired in a fast firing kiln of laboratory in the temperatures of 900 ºC, 950 ºC, 1000 ºC, 1050 ºC, 1075 ºC and 1100 ºC, with heating rate of 40 ºC/min, a set of bodies test was fired at 950 ºC, however with heating rate of 20 ºC/min, for the checking of the influence of the time of firing range in the coloration of the ceramic plates. The time of firing range showed not to intervene significantly in the alteration of the color and the test bodies produced significant alterations in the temperature of 1000 ºC, acquiring, respectively the shades: orange, red and dark brown. The color change was followed in intensity equivalent for the linear retraction of firing, for the water's absorption and mechanical strength.